2006
DOI: 10.1080/10473289.2006.10464562
|View full text |Cite
|
Sign up to set email alerts
|

The Adsorptive Capacity of Vapor-Phase Mercury Chloride onto Powdered Activated Carbon Derived from Waste Tires

Abstract: Injection of powdered activated carbon (PAC) upstream of particulate removal devices (such as electrostatic precipitator and baghouses) has been used effectively to remove hazardous air pollutants, particularly mercurycontaining pollutants, emitted from combustors and incinerators. Compared with commercial PACs (CPACs), an alternative PAC derived from waste tires (WPAC) was prepared for this study. The equilibrium adsorptive capacity of mercury chloride (HgCl 2 ) vapor onto the WPAC was further evaluated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The spent sorbents were placed in an open platinum pan and the experiments conducted in N 2 at a flow rate of 50 mL min −1 . Different from the work of Lin which kept the temperature at certain degree [12], nominal heating rate of 20 K min −1 was employed to increase the desorption temperature from 293 K to 1073 K and continuous records of temperature and sorbent weight were taken. The vapor-phase Hg 0 concentrations were analyzed continuously using a SG-921 cold vapor atomic absorption spectroscopy (CVAAS).…”
Section: Analytic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The spent sorbents were placed in an open platinum pan and the experiments conducted in N 2 at a flow rate of 50 mL min −1 . Different from the work of Lin which kept the temperature at certain degree [12], nominal heating rate of 20 K min −1 was employed to increase the desorption temperature from 293 K to 1073 K and continuous records of temperature and sorbent weight were taken. The vapor-phase Hg 0 concentrations were analyzed continuously using a SG-921 cold vapor atomic absorption spectroscopy (CVAAS).…”
Section: Analytic Methodsmentioning
confidence: 99%
“…Lin et al used TGA to determine the adsorptive capacity and adsorption isotherm of vapor-phase mercury chloride on powdered activated carbon [11,12]. In this study, we used TGA to analyze the adsorbed mercury species of spent sorbents.…”
Section: Mercury Adsorption Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…The capabilities of the elemental sulfur diffusing into the mesopores and macropores of the activated carbons were significantly different at temperatures of 400 and 650 C, resulting in a clear dissimilarity in the sulfur content of the activated carbons. Moreover, some studies have reported a mass ratio of carbon and sulfur of 1:4 (Hladíková et al, 2001); however, the aforementioned research showed that the adsorptive capacity of sulfur-impregnated activated carbons produced at the carbon-to-sulfur mass ratio of 1:3 was superior to 1:0.5, 1:1, 1:2, and 1:4 (Lin et al, 2006). Thus, the experiments conducted in this study used sulfur-impregnated activated carbons produced at the carbon-to-sulfur mass ratio of 1:3.…”
Section: Sample Preparation and Characterizationmentioning
confidence: 96%
“…reacted with sulfide ions (S 2-) to generate stable mercuric sulfide precipitate under the condition of weak alkaline,[46] and the Hg 2+ removal principle can be fully explained by the equation(7).…”
mentioning
confidence: 99%